Factors associated with willingness to engage in responsible smartphone disposal behaviors: Towards user-centric policies for sustainable smartphone management - Donghun Kang; Moon Choi (Cleaner and Responsible Consumption, 2025)
The short replacement cycle of smartphones generates substantial electronic waste, with many disused devices stored rather than disposed of responsibly. This study explores factors associated with the willingness to engage in responsible disposal. An online survey of South Korean adults (N = 943) assessed preferences for four disposal methods: (a) manufacturer trade-ins, (b) transfers to family/friends, (c) C2C sales, and (d) C2B sales. Non-disposal was prevalent, with 85.8 % storing an average of 2.0 smartphones. Trade-ins (31.9 %) were the most preferred method, followed by transfers (22.3 %), C2C sales (16.4 %), and C2B sales (15.5 %). Ordered logistic regression showed subjective norms, response efficacy, and disposal knowledge positively influenced willingness to dispose, while emotional attachment hindered disposal except for transfers. Findings suggest raising awareness and addressing emotional attachment can promote responsible recycling, reducing smartphone hoarding and enhancing sustainability.